Development of Energy Harvesting from Raindrop - Fauzi Omar, Mohamad; Che Mat Haris, Harizan; Aminudin, Norziana (International Journal of Engineering and Technology, 2019)
This paper presents an experimental study of harvesting from the mechanical energy produce from raindrop. The energy is harvested using round piezoelectric transducer disc that is installed horizontally with the raindrop. This project aims to produce a simple prototype of raindrop power generator by using multiple numbers of piezoelectric transducers. The raindrop power generator major components are consisting of water pump, water tank, piezoelectric plane, and raindrop maker. Each piezoelectric transducer has the diameter size of 25mm. This projects analyses the energy produced with increasing number of piezoelectric transducer with the total diameter ranging from 25mm, 50mm, 75mm, 100mm and 125mm respectively. The piezoelectric trandsducer with the diameter of 125mm will produce and harvest the highest output voltage, current, and energy compared to the other diameters of the piezoelectric transducer. The highest output voltage and current harvested for the piezoelectric transducer of 125mm is 3.3V and 0.47mA respectively. The energy produced from the piezoelectric transducer was determined through calcultion. In this case the output energy produced was 54.45Î¼J.Â Â